2010
DOI: 10.3350/kjhep.2010.16.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of gas-forming liver abscesses: comparison between diabetic and nondiabetic patients

Abstract: Gas-forming liver abscesses are not uncommon in cases of pyogenic liver abscesses and are associated with high morbidity and mortality rates. The clinical manifestations and complications do not differ significantly between DM and non-DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
4
7
0
Order By: Relevance
“…In this study, gas‐forming abscesses in the DM and non‐DM groups accounted for 11.4% and 5.0% of the PLA cases, respectively. This difference was statistically significant; therefore, DM patients are more susceptible to gas‐forming abscesses, and this conclusion confirms previous findings [12,23–28]. Diabetic patients, especially patients whose plasma glucose is poorly controlled, provided a beneficial environment for the growth of gas‐forming microorganisms.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, gas‐forming abscesses in the DM and non‐DM groups accounted for 11.4% and 5.0% of the PLA cases, respectively. This difference was statistically significant; therefore, DM patients are more susceptible to gas‐forming abscesses, and this conclusion confirms previous findings [12,23–28]. Diabetic patients, especially patients whose plasma glucose is poorly controlled, provided a beneficial environment for the growth of gas‐forming microorganisms.…”
Section: Discussionsupporting
confidence: 89%
“…Compared to the past, patients now have more underlying co‐morbidities and there is an increasing incidence of underlying malignancy. Similar data from Denmark, Korea and America also indicated a rising trend of T2DM and malignancy amongst PLA patients . As compared to the earlier data (1993–1997), there is a sharp increase in PLA mortality rate (from 0% to 13%) and this is likely secondary to patients presenting sicker, in a poorer physiological state and immuno‐compromised with underlying T2DM.…”
Section: Discussionsupporting
confidence: 70%
“…2,5,6 However, some studies from Southern Korea and Denmark reported opposite results. 3,4,18 We consider that PLA shows some unique characteristics in the population of Taiwan. Further epidemiological comparisons among other populations are indicated for PLA.…”
Section: Parametersmentioning
confidence: 99%